Analyzing the impact of land use change on flood risk and social vulnerability using SCS-CN method and GIS - Yulaichah (ASEAN Natural Disaster Mitigation and Education Journal, 2026)
Background: Urban flooding has emerged as a chronic environmental challenge in Malang City, contradicting its geomorphological advantage as a highland region. This persistent phenomenon is fundamentally driven by rapid urbanization within the Bango Sub-watershed, where the massive conversion of permeable landscapes into impervious surfaces has severely disrupted the local hydrological balance. Understanding the complex interplay between physical landscape alterations and social demographic pressures is essential for formulating effective disaster mitigation strategies. Methods: This study employs a comprehensive quantitative spatial approach, integrating Geographic Information Systems (GIS) with the Soil Conservation Service Curve Number (SCS-CN) method to model surface runoff volumes and map flood hazards. Land use classification was conducted using Support Vector Machine algorithms on high-resolution satellite imagery to ensure precision. Uniquely, this research incorporates a social dimension through the calculation of the Settlement Carrying Capacity (DDPm) index to assess the sustainability of population density relative to the availability of safe land. Findings: The analysis demonstrates a significant positive correlation between the expansion of built-up areas and the magnitude of flood hazards. Areas dominated by commercial buildings and dense settlements exhibit extreme Curve Number values, identifying Blimbing and Lowokwaru Districts as critical runoff generators. The study reveals a severe carrying capacity deficit in the city center, where population pressure forces settlements to expand into disaster-prone river border zones, creating "hotspots" that combine high physical hazard with acute social vulnerability. Conclusion: It is concluded that the escalation of flood risk in the Bango Sub-watershed is an anthropogenic consequence of spatial planning mismanagement, rather than mere natural meteorological variability. Sustainable mitigation demands a paradigm shift from purely structural engineering to rigorous land use management, emphasizing the enforcement of river regulations and runoff retention policies. Novelty/Originality of Article: This article offers a novel methodological framework by synthesizing hydrological modeling with settlement carrying capacity assessment. Unlike traditional studies that isolate physical risks, this research explicitly links runoff dynamics with demographic pressures, providing a holistic perspective on how social demand for housing drives land conversion and amplifies disaster vulnerability in rapidly developing urban watersheds.